2020
DOI: 10.21203/rs.2.22707/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-Term Outcomes of Mirogabalin in Patients with Peripheral Neuropathic Pain: A Retrospective Study

Abstract: Background: Mirogabalin, which is approved for the treatment of peripheral neuropathic pain in Japan, is a ligand for the α2δ subunit of voltage-gated calcium channels. Both pregabalin and mirogabalin act as nonselective ligands at the α2δ-1 and α2δ-2 subunits. Mirogabalin has a unique binding profile and long duration of action. Pregabalin has been reported to produce intolerable adverse effects in some patients. This study investigated outcomes associated with mirogabalin administration in patients with peri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Recently, Tetsunaga et al reported their retrospective, single‐arm, single‐centre experience with mirogabalin in 187 DPNP patients 28 . All studied patients had switched from pregabalin to mirogabalin owing to reasons of absence of therapeutic responses or occurrence of side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Tetsunaga et al reported their retrospective, single‐arm, single‐centre experience with mirogabalin in 187 DPNP patients 28 . All studied patients had switched from pregabalin to mirogabalin owing to reasons of absence of therapeutic responses or occurrence of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they found the Recently, Tetsunaga et al reported their retrospective, singlearm, single-centre experience with mirogabalin in 187 DPNP patients. 28 All studied patients had switched from pregabalin to mirogabalin owing to reasons of absence of therapeutic responses or occurrence of side effects. Overall, pain NRS scores were substantially reduced after 1 week of mirogabalin and continued to reduce even further over the course of therapy.…”
Section: F I G U R E 17 the Risk Of Peripheral Oedema Between Mirogab...mentioning
confidence: 99%
“…Tetsunaga et al reported good clinical outcomes of mirogabalin administration in patients with PNeP who discontinued pregabalin treatment due to AEs or lack of efficacy, although the participants of this study were not limited to those with spine diseases6) . Akazawa et al first reported the clinical outcomes of mirogabalin administration in patients with PNeP due to spinal diseases who discontinued pregabalin treatment.…”
mentioning
confidence: 85%
“…According to previous studies, switching from pregabalin to mirogabalin in patients with PNeP resulted in good clinical outcomes [5][6] . Mirogabalin administration for PNeP due to lumbar spine disease is effective in improving leg symptoms, low back pain, and sleep disturbance 7) .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation